Development of Animation-Based Learning Videos for Science and Technology Subjects in Class IV Elementary School - tanjung, Yudi aksan; Hidayati, Abna; Zen, Zelhendri; Hendri, Nofri (JUPE : Jurnal Pendidikan Mandala, 2023)
The development of learning video media was motivated by the lack of auxiliary media in education, the lack of educator expertise in improving educational media, thus affecting student learning outcomes. In order to address these problems, animation-based learning media was developed. This research aims to create educational media products that are valid, practical and effective in learning. This type of research adopts a development research design known as Research and Development (R&D). by exploring the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. The product validity test was carried out by three validators, namely one material expert validator and two media expert validators. The practicality test was tried on 22 class IV students at SD Negeri 26 Air Tawar Timur with the aim of finding out the practicality of the product. After that, the pre-test and post-test scores are used to calculate the effectiveness of the media being developed. The product validity test results from validator I found a value of 4.93 with a very valid group. The product validity test from validator II found a value of 4.83 with a very valid category. Next, validation of the material was attempted by the subject teacher; Science and Technology obtained a score of 4.83 with a very valid category. Next, the results of the product practicality test that were tried by fourth grade elementary school students obtained an average score of 4.65 in the very practical category. After that, an effectiveness test was tried by obtaining a Sig value. p value 0.00 -; 0.05, so the use of this learning media is declared effective because there is a significant comparison between the learning scores before and after using educational media. It can be concluded that educational media uses animation-based educational videos that have been developed to be valid, practical and effective for use in science lessons